(untitled) (KYAMC Journal, 2025)
Background: The role of oncogenes and tumor suppressor genes in Oral squamous cell carcinoma (OSCC) have already been found in numerous studies. Astrocyte Elevated Gene-1(AEG-1) is an oncogene that is overexpressed in many cancer, including OSCC. Objective: With an aim of understanding the genetic basis of squamous cell carcinoma among the Bangladeshi population, this study has been carried out to find out the genetic expression in AEG-1 gene with OSCC patients. Materials and Methods: Malignant tissue was collected from 24 patients with OSCC and 14 normal patients. RNA was extracted using RNeasy Mini Kit(Qiagen). Then, cDNA synthesis and RT-qPCR were performed to find out the expression of AEG-1 gene. Results: Among twenty four patients, fourteen patients(58.3%) with OSCC had over-expression of AEG-1 gene in compared to control, which was 3 fold increased in OSCC patients. Conclusion: In sum, according to the study, it has been indicated that the over-expression of the AEG gene has an oncogenic role in development of OSCC in Bangladeshi patients. However, further studies on the expression of the AEG-1 gene have to be done with more samples for a better understanding of their role in the formation of OSCC. KYAMC Journal Vol. 16, No. 01, April 2025: 30-36